SAV Nsp2 regulates NF-κB signaling to induce inflammatory responses by targeting host DDX3 - Gao, Shuai; Han, Bing; Xu, Baoxing; Wang, Na; Zhang, Yanru; Liu, Xuefei; Zhang, Mengmeng; Wang, Guanbo; Guan, Xueting; Huang, Jinshan; Liu, Min; Shi, Wen (Developmental & Comparative Immunology, 2023)
Salmon alphavirus (SAV) infection leads to severe pancreas disease (PD) with typical inflammatory responses in Atlantic salmon (Salmo salar) and rainbow trout (Oncorhynchus mykiss). Nsp2, an important nonstructural protein of SAV, can activate NF-κB signaling pathway to reduce inflammatory responses. However, the molecular mechanism remains unclear. In this study, the ML (279-421aa) of Nsp2 was revealed to be the key domain for activating NF-κB. We focused on a host protein, DEAD-box RNA helicase 3 (DDX3), that may interact with Nsp2 to regulate NF-κB-induced inflammatory. The interaction between DDX3 and Nsp2 was confirmed in vitro. Overexpression of DDX3 inhibited the activation of NF-κB by Nsp2. SAV Nsp2 relieves the inhibitory effect of DDX3 on NF-κB, thereby initiating the innate immune response. This study revealed the molecular mechanism of Nsp2-induced inflammatory response by targeting DDX3 to activate NF-κB, providing a theoretical basis for revealing the underlying infection mechanism and pathogenesis of SAV.